1991
DOI: 10.1159/000480550
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Intramuscular Vitamin E in Premature Babies

Abstract: Vitamin E (α-toxopherol) is widely used, at different dosages and schedules and in different formulations, in neonatal intensive care units to prevent intraventricular hemorrhage, retrolental fibroplasia, bronchopulmonary dysplasia and hemolytic anemia of preterm infants. As part of a wider project to assess the effect of vitamin E, the present study was designed to determine whether the only intramuscular formulation available today in Italy and in other European countries (olive oil solution), and widely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Due to the relatively higher density of skeletal-muscle capillaries in neonates, water-soluble drugs show an increased intramuscular absorption, e.g., absorption of amikacin ( Kafetzis et al, 1979 ). Whether this is also the case for preterm neonates is unknown, but the example of intramuscular administration of vitamin E acetate in a lipophilic preparation, showed that the ester was never systematically detectable in premature neonates as opposed to E-vitamin delivered in an aqueous preparation ( Italian Collaborative Group on Preterm Delivery, 1991 ).…”
Section: Drug Disposition In Premature Neonatesmentioning
confidence: 99%
“…Due to the relatively higher density of skeletal-muscle capillaries in neonates, water-soluble drugs show an increased intramuscular absorption, e.g., absorption of amikacin ( Kafetzis et al, 1979 ). Whether this is also the case for preterm neonates is unknown, but the example of intramuscular administration of vitamin E acetate in a lipophilic preparation, showed that the ester was never systematically detectable in premature neonates as opposed to E-vitamin delivered in an aqueous preparation ( Italian Collaborative Group on Preterm Delivery, 1991 ).…”
Section: Drug Disposition In Premature Neonatesmentioning
confidence: 99%